Glycerol in energy transportation: a state-of-the-art review. Issue 20 (7th October 2021) - Zhang, Tianjian; Liu, Changhui; Gu, Yanlong; Jérôme, François
Abstract : Glycerol-containing fluid was used as a novel and functional energy transport medium. Abstract : Glycerol, which bears green, low-cost, and good miscibility features, provides a variety of solvent portfolios to satisfy the complex market demands. Owing to its abundant feedstock and unique properties, glycerol is a good candidate in catalysis, high-value-added chemical conversion, and solvents. It can also be used as an energy transportation medium attributed to its high boiling temperature, promising thermal stability, and fertile hydrogen bond. Despite the great potential of glycerol in energy transportation, a review paper that summarizes and discusses its recent advances is blank to date. In this review paper, recent advances in the utilization of glycerol and glycerol-based mixture solvent systems in energy transportation were summarized. Thermophysical properties of glycerol-containing fluids, including their performance in various heat transfer occasions, and principles of related energy transportation were comprehensively introduced and discussed. Applications of these fluids in industrial processes were also discussed systematically. Furthermore, advantages and drawbacks of glycerol in energy transportation were concluded. It opens an important avenue to alleviate the backlog of glycerol production by means of valuable applications.